A escrita da história entre dois mundos: uma análise da produção de Alice Piffer Canabrava (1935-1961) - Erbereli Júnior, Otávio [UNESP] (2014)
On this dissertation, we pervade the historiographical production of Alice Piffer Canabrava (1911-2003) from the major concerns of History of Historiography. We privilege the period comprehended between 1935, the year of Canabrava‘s join in the Geography and History‘s graduation on the Faculty of Philosophy, Sciences and Letters (FFCL) of São Paulo University (USP), and, 1961, the foundation year of the Higher Education Professores on History Association (APUH), in the FFCL of Marília-SP. We have tried to comprehend Alice Piffer Canabrava‘s Writing History trough the notion of Michel De Certeau‘s historiographical operation. The Canabrava‘s formative place, which is, the several Chairs‘ classes of the V sub section on Geography and History of II Sciences section of USP‘s FFCL during the period in which she was a student, between 1935 and 1937, helped us to comprehend her choices and historiographical practices, like her notions of History and Document, as well as a long term mobilization knowledge: the vidalian Geography. We also have demarcated the 1946‘s competition for the American Civilization History as the focal point of Alice Canabrava‘s intellectual trajectory, once after having been deprecated on this event, settled down on the Faculty of Administration and Economics Sciences, founded in the same year. This new place provided her aids to incorporate Economics on her historiographical production. We expect that this work can contribute to the comprehension of a special moment the History of Historiography: the constitution of university historiographical production